Multi-target therapeutics for neuropsychiatric and neurodegenerative disorders. Issue 12 (December 2016) - Bawa, Priya; Pradeep, Priyamvada; Kumar, Pradeep; Choonara, Yahya E.; Modi, Girish; Pillay, Viness
Graphical abstract: Highlights: The polygenic nature of neuro-affected disorders favors multi-targeted drug design. Revisions of major diagnostic systems support DMLs for neuropsychiatric disorders. The difficulty titrating specific DML activities is an impediment to the approach. Abstract : Historically, neuropsychiatric and neurodegenerative disease treatments focused on the 'magic bullet' concept; however multi-targeted strategies are increasingly attractive gauging from the escalating research in this area. Because these diseases are typically co-morbid, multi-targeted drugs capable of interacting with multiple targets will expand treatment to the co-morbid disease condition. Despite their theoretical efficacy, there are significant impediments to clinical success (e.g., difficulty titrating individual aspects of the drug and inconclusive pathophysiological mechanisms). The new and revised diagnostic frameworks along with studies detailing the endophenotypic characteristics of the diseases promise to provide the foundation for the circumvention of these impediments. This review serves to evaluate the various marketed and nonmarketed multi-targeted drugs with particular emphasis on their design strategy. Teaser: Despite the inconclusive pathophysiology of neuropsychiatric and neurodegenerative diseases, treatment by multi-targeted drugs has significant potential. Although they have yet to outshine the 'magic bullets', new diagnostic techniques and endophenotype studies suggest imminent success in this field.